2018
DOI: 10.1111/ctr.13407
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Angiotensin II type I‐receptor antibodies in transplant glomerulopathy

Abstract: AT R-Ab showed no independent prognostic role in TG in this pilot analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Alternatively, several studies have suggested the presence of DSA other than anti-HLA antibodies, 6 with many different antigens as their targets. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, several studies have suggested the presence of DSA other than anti-HLA antibodies, 6 with many different antigens as their targets. 7 …”
mentioning
confidence: 99%
“…Alternatively, several studies have suggested the presence of DSA other than anti-HLA antibodies, 6 with many different antigens as their targets. 7 Treatment of cAMR is an unmet need, considering that late allograft dysfunction is predominantly related to this condition, and no specific treatment has been approved to date. 1,8 The anti-interleukin (IL)-6 receptor antibody tocilizumab (TCZ) has been used in cAMR with promising results in reducing alloantibodies, ameliorating rejection lesions, and slowing renal function deterioration, 9 as also documented by our group.…”
mentioning
confidence: 99%